Pengaruh Pertumbuhan Kacang Hijau (phaseolus radiatus) dengan Perlakuan Pemberian Media Air Berbeda-beda di Kelas 5 Mi Al Fattah Bumiharjo - Eka Maulidia; Muhammad Suwignyo Prayogo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Mung bean (Phaseolus radiatus L.) is an important agricultural commodity in Indonesia, widely cultivated due to its short harvest period, drought tolerance, and high nutritional value. However, the increasing demand for mung beans has not been matched by optimal production, necessitating innovations in cultivation techniques, particularly in water management. This study aims to examine the effect of different volumes of water media on the growth of mung beans. The research employed an experimental method using a Completely Randomized Design (CRD), involving nine mung bean seeds divided into three treatments with water volumes of 10 cc, 15 cc, and 20 cc, each replicated three times. Observations were conducted over seven days, focusing primarily on plant height. Analysis of variance (ANOVA) revealed significant differences (p < 0.05) among treatments. The 15 cc water volume resulted in the best growth, indicated by the highest average plant height at the end of the observation period, while 10 cc and 20 cc volumes produced less optimal growth. Insufficient water caused drought stress, whereas excessive water led to overly saturated media that impaired root respiration. This study underscores the importance of proper water volume regulation in mung bean cultivation to support optimal growth and prevent yield losses.